Relationship Between Sleep Duration, Sleep Quality and Daytime Physical Activity - Makikawa, Masaaki; Wang, Tianyi; Masuda, Hazuki; Okada, Shima; Nakauchi, Koki (Transactions of Japanese Society for Medical and Biological Engineering, 2021)
We examined the relationship between the sleep duration and subjective waking sleep duration quality and the amount of physical activity during the day in university students. Twelve healthy subjects (21.1 ± 1.6 y.o.) measured daytime physical activity and nighttime sleep duration using a wearable device for 1 month, and subjective sleep duration quality scores were calculated using the OSA sleep questionnaire MA version.Weak positive correlation between calorie consumption and sleep duration was found in the group of males (above the standard activity). Weak negative correlation was found between calories consumption and sleep duration and subjective sleep duration quality scores in the group of females (above the standard activity). This finding may indicate there are sex differences in the relationship between sleep duration and physical activity. Consuming calories above standard leads to longer sleep duration in males, and shorter sleep duration and better subjective sleep duration quality in females.